Lipopolysaccharide-unresponsive mutant pre-B-cell lines blocked in NF-kappa B activation. - Briskin, M (1990)
NF-kappa B activation is a crucial late step in the induction of immunoglobulin kappa light-chain gene expression in pre-B cells by lipopolysaccharide (LPS). We have analyzed NF-kappa B activation in three independent mutant lines of 70Z/3 pre-B cells which are unresponsive to LPS. All three variant cell lines failed to activate NF-kappa B when induced with LPS or the phorbol ester 12-O-tetradecanoylphorbol 13-acetate. However, all three cell lines contained functional NF-kappa B, as revealed by detergent treatment of cytoplasmic extracts. Moreover, cycloheximide induced limited activation of NF-kappa B comparable to that in wild-type 70Z/3 pre-B cells in two of the three variant lines. These results indicate that the mutations blocking kappa gene induction in these variant 70Z/3 pre-B-cell lines affect NF-kappa B activation.